Desert borderland : the making of modern Egypt and Libya - Ellis, Matthew H. (Stanford University Press, 2018)
'Desert Borderland' investigates the historical processes that transformed political identity in the easternmost reaches of the Sahara Desert in the half century before World War I. Adopting a view from the margins - illuminating the little-known history of the Egyptian-Libyan borderland - the text challenges prevailing notions of how Egypt and Libya were constituted as modern territorial nation-states. Matthew H. Ellis draws on a wide array of archival sources to reconstruct the multiple layers and meanings of territoriality in this desert borderland.